Ethanologens vs. acetogens: Environmental impacts of two ethanol fermentation pathways. (December 2015) - Budsberg, Erik; Crawford, Jordan; Gustafson, Rick; Bura, Renata; Puettmann, Maureen
Abstract: Bioconversion production of ethanol from cellulosic feedstock is generally proposed to use direct fermentation of sugars to ethanol. Another potential route for ethanol production is fermentation of sugars to acetic acid followed by hydrogenation to convert the acetic acid into ethanol. The advantage of the acetogen pathway is an increased ethanol yield; however, using an acetogen requires the additional hydrogenation, which could substantially affect the life cycle global warming potential of the process. Assuming a poplar feedstock, a cradle to grave Life cycle assessment (LCA) is used to evaluate the environmental impacts of an acetogen based fermentation pathway. An LCA of a fermentation pathway that uses ethanologen fermentation is developed for comparison. It is found that the ethanologen and acetogen pathways have Global Warming Potentials (GWP) that are 92% and 46% lower than the GWP of gasoline, respectively. When the absolute GWP reduction compared to gasoline is calculated using a unit of land basis, the benefit of the higher ethanol yield using the acetogen is observed as the two pathways achieve similar GWP savings. The higher ethanol yield in the acetogen process plays a crucial role in choosing a lignocellulosic ethanol production method if land is a limited resource. Highlights: Life cycle assessment of a new high yielding ethanol bioconversion process. Environmental impacts of standard and high yielding ethanol routes are compared. Relative and absolute global warming potential reductions are calculated. Relative global warming potential reductions are significantly different. Both pathways have similar absolute global warming potential reductions.